An investigation of colonialism in the novels of Nadine Gordimer and Anita Desai - Thomas, Elizabeth (University of Limpopo, 2002)
The purpose of this study is to investigate colonialism in the novels of Nadine Gordimer and Anita Desai. A further purpose is to introduce these two major writers to a wider audience, thereby illuminating not only their work but also the artistic, social and moral assumptions on which it rests. A comparative study of the novels of Gordimer and Desai shows how these writers, from socially and culturally different countries, reflect and explore colonialism. By locating this phenomenon of world history in Post-Colonial Literary Studies the project calls for a discussion of the various critical models of post-colonial writing. In consequence, the study moves beyond the dichotomy of east-west and centre-periphery to a reading of Gordimer's and Desai's novels at several levels, with a particular focus on India's special experience of colonialism - both at home and abroad -and Gordimer's status as a white South African. From this perspective evolves the notion that Desai and Gordimer reveal through their texts patterns of similarity and difference in their respective colonial encounters. If we were to search for a writer from Africa whose being and writing have been directly involved with issues pertaining to the historical phenomena of colonialism and race struggle over an extended period, then Gordimer must be the ideal candidate. She is a writer deeply bound up with the multiple phases and consequences of South African apartheid. Also, she is someone who tries to go beyond history to depict the conscience of the age by writing about the human condition in times of terror and fear. A contemporary analysis of the human condition is a concern that Gordimer and Desai share as writers of fiction. The agony of a post colonial India that tries to liberate itself from the dialectic of history is reflected in Desai's novels in the framework of "difference on equal terms". This places her in the "second generation" of lndo-English writers who write from the hybridised and syncretic view of the modern world that celebrates cultural cross-pollination. A special achievement of Gordimer and Desai is to succeed in powerfully portraying female characters in a rapidly changing world, though each writer explores the place of women in society from her own cultural perspective. Writers are transmitters of their cultures. A study of this kind, I hope, will help to stimulate interest and enjoyment in the reading of South African and Indian literature and thus strengthen the literary bond of understanding between the two countries.
Thesis (PhD. (English Studies)) --University of Limpopo, 2002.
Keywords: Colonialism; Novels; Postcolonialism in the literature; Literature -- History and criticism